Agricultural pesticide abuse in Texas: A case study in the mobilization of law - Rhoades, Cecilia C. (American journal of criminal justice, 1993)
This article focuses on why and how law was mobilized to regulate agricultural pesticide abuse in Texas during the 1980s. Pesticide abuse is defined as a significant, violent corporate crime worthy of additional analysis. The dynamic forces leading to development of reactive and proactive mobilization efforts are examined. Black’s propositions that proactive law becomes the major form of mobilization in regard to generalized social needs, in conflict situations, and in protection of society’s lower strata are confirmed. Restraints and limits on legal mobilization are discussed.